Interoperability, safety and security in IoT : third International Conference, InterIoT 2017, and fourth International Conference, SaSeIot 2017, Valencia, Spain, November 6-7, 2017, Proceedings /: third International Conference, InterIoT 2017, and fourth International Conference, SaSeIot 2017, Valencia, Spain, November 6-7, 2017, Proceedings. (2018) - Unknown
No abstract available